(untitled) (Journal of Pharma Insights and Research, 2025)
Pimenta dioica, also called as Allspice or Jamaica pepper, serves as a prominent species within the Myrtaceae family, celebrated for its complex phytochemical profile and diverse utility. Native to the Caribbean and Central America, this evergreen tree has transcended its traditional culinary boundaries to become a subject of significant scientific interest. The plant possesses a rich array of bioactive constituents, particularly eugenol, which underpins its extensive pharmacological and biological activities. In traditional medicine systems, extracts from the leaves and berries are utilized to alleviate gastrointestinal distress, respiratory conditions, and musculoskeletal ailments. Current research has further described its potent agro-biological roles, demonstrating efficacy as an eco-friendly alternative to synthetic pest control agents. Essential oils derived from the plant exhibit marked anti-helminthic, larvicidal, insecticidal, and nematicidal properties, offering sustainable solutions for pest management in agriculture and public health. Moreover, recent investigations into aquaculture have positioned P. dioica as a functional feed additive, capable of enhancing growth performance, augmenting immune responses, and mitigating stress in fish species such as Oreochromis mossambicus. This article summarizes the current scientific knowledge regarding the applications of P. dioica, analyzing its therapeutic potential alongside its emerging roles in sustainable agriculture and aquaculture, thereby showing its value as a renewable biological resource